Magic tree house Diving with dolphins - Osborne, Mary Pope (Red fox London, 2009)
Diving deep underwater in a mini-sub, they have to tackle a giant octopus and escape from a scary shark. The dolphins seem very friendly, but will they help Jack and Annie find the answer to the puzzle